Curated collection for clinician educators: Six key papers on residency recruitment. Issue 2 (30th April 2021) - Schnapp, Benjamin H.; Alvarez, Al'ai; Bianchi, Riccardo; Caretta‐Weyer, Holly; Jewell, Corlin; Kalantari, Annahieta; Lee, Eric; Miller, Danielle; Quinn, Antonia
Abstract: Introduction: All emergency medicine (EM) residency programs must recruit new medical school graduates each year. The process is often overwhelming, with each program receiving far more applicants than available positions. We searched for evidence‐based best practices to guide residency programs in screening, interviewing, and ranking applicants to ensure a high‐performing and diverse residency class. Methods: A literature search was conducted on the topic of residency recruitment, utilizing a call on social media as well as multiple databases. After identifying relevant articles, we performed a modified Delphi process in three rounds, utilizing junior educators as well as more senior faculty. Results: We identified 51 relevant articles on the topic of residency recruitment. The Delphi process yielded six articles that were deemed most highly relevant over the three rounds. Transparency with selection criteria, holistic application review, standardized letters of evaluation, and blinding applicant files for interviewers were among noted best practices. Conclusions: Well‐supported evidence‐based practices exist for residency recruitment, and programs may benefit from understanding which common recruitment practices offer the most value. The articles discussed here provide a foundation for faculty looking to improve their program's recruiting practices.